Weisse Raben - Alptraum Tschetschenien - Feindt, Johann; Trampe, Tamara (Germany : Kufus, Thomas, 2005)
Petya and Kiril signed up as volunteers in the army at age 18 and set off for service in Chechnya. Katya worked as a nurse in a field hospital in the war zone. When they returned home from the Caucasus, none of them was the same as before. They were psychologically and emotionally and their lowest point, alone with memories of war, of death and suffering. In the course of three years Johann Feindt and Tamara Trampe followed the attempts of these young people to fit into society again after their return from war, a society which acted as if the war in Chechnya did not exist. Only in the Committee of Mothers of Russian Soldiers can these returnees from the war and their helpless parents fnd similarly stricken people, with whom they can find mutual understanding.
Duration: 01:32:00
Keywords: Documentary films